Ice hockey skating sprints: run to glide mechanics of high calibre male and female athletes - Budarick, A. R.; Shell, J. R.; Robbins, S. M. K.; Wu, T.; Renaud, P. J.; Pearsall, D. J. (Sports Biomechanics, 2020)
The skating acceleration to maximal speed transition (sprint) is an essential skill that involves substantial lower body strength and effective propulsion technique. Coaches and athletes strive to understand this optimal combination to improve performance and reduce injury risk. Hence, the purpose of this study was to compare body centre of mass and lower body kinematic profiles from static start to maximal speed of high calibre male and female ice hockey players on the ice surface. Overall, male and female skaters showed similar centre of mass trajectories, though magnitudes differed. The key performance difference was the male`s greater peak forward skating speed (8.96 ± 0.44 m/s vs the females`8.02 ± 0.36 m/s,p< 0.001), which was strongly correlatedto peak leg strength (R2= 0.81). Males generated greater forwardacceleration during the initial accelerative steps, but thereafter, both sexes had similar stride-by-stride accelerations up to maximal speed. In terms of technique, males demonstrated greater hip abduction (p= 0.006) and kneeflexion (p= 0.026) from ice contact to push off throughout the trials. For coaches and athletes, these findings underscore the importance of leg strength and widely planted running steps during the initial skating technique to achieve maximal skating speed over a 30 m distance.